(untitled) (Colombia Medica, 2021)
Objective: This study aimed to correlate the genetic profile of the NUDT15 and TPMT genes with the side effects of the treatment of pediatric patients with acute lymphoid leukemia who were undergoing maintenance therapy at a tertiary care hospital in 2017. Methods: This was an analytical, longitudinal, observational study in which the genotypes of the genes of interest were determined by PCR allelic discrimination with TaqMan® probes in patients receiving chemotherapy during the maintenance phase in the Pediatric Hematology and Oncology Unit in 2017. Sociodemographic and clinical data corresponding to the first six months of their maintenance chemotherapy were collected, and the correlation between the genotypes obtained and the development of side effects during the maintenance phase of chemotherapy in these patients was evaluated. Results: Seventy pediatric patients were included in the study. Genetic analyses were carried out of these for NUDT15 and TPMT (rs1800462 and rs1800460) on 68 patients, while for the rs1142345 polymorphism, typing was achieved in 42 patients. 4/68 patients were heterozygous for NUDT15, and the same number of patients were heterozygous for rs1800462 and rs1142345, while for rs1800460, 6 heterozygous patients were identified. No statistically significant association was identified between the genetic variants and the outcomes of interest. Conclusion: Studies with a larger population size are needed and the evaluation of other genetic variants that may influence the development of side effects during maintenance chemotherapy.